Impact of Promotion Mix on Grabfood Merchant Customer Purchase Decision in Jabodetabek - Gagih Pradini; Nava Annisya Febrianti; Anisa Putri Kusumaningrum (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The impact of the Covid-19 pandemic made the increase of online-based culinary businesses and caused the desire and need for food and beverage ordering also increased. This research activity will discuss customer purchase decisions at Grabfood merchants in Jabodetabek with quantitative methods using testing techniques validity, reliability, classical assumptions, model feasibility, and Analysis Regression Linear Multiple and in the collection of research samples conducted applying accidental sampling with survey methods through Questionnaires distributed as many as 40 samples as research instruments to find out respondents' opinions on the impact of promotion mix with variables Ads, Promotions, and Publicity. The results of the study in the form of data on the impact of Advertising, Promotion, Publicity that affect significantly and positively on customer purchase decisions, this is supported by 81.4% of respondents who choose the Grabfood application as a means or medium to buy food and the intensity of increased promotions made by merchants or parties.  Grabfood applicator itself. Based on the results of significant research it was found that Promotion Mix with subvariable Advertising, Promotion, and Publicity had a significant and positive effect on customer purchase decisions at Grabfood Merchant in Jabodetabek.